2017
DOI: 10.1007/s10551-017-3504-8
|View full text |Cite
|
Sign up to set email alerts
|

Linking Platforms, Practices, and Developer Ethics: Levers for Privacy Discourse in Mobile Application Development

Abstract: Privacy is a critical challenge for corporate social responsibility in the mobile device ecosystem. Mobile application firms can collect granular and largely unregulated data about their consumers, and must make ethical decisions about how and whether to collect, store, and share these data. This paper conducts a discourse analysis of mobile application developer forums to discover when and how privacy conversations, as a representative of larger ethical debates, arise during development. It finds that online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 37 publications
(32 reference statements)
1
29
0
1
Order By: Relevance
“…These results are similar to a study that was carried out 15 years previous, which indicates stagnation in engineer's mindsets [17]. Beyond interviews, a discourse analysis of two mobile developer forums for privacy relevant conversations found that developers of these forums were concerned about how third-parties are collecting data, the privacy implications of features requested by end-users, and the legal consequences of their actions [60].…”
Section: Privacy and Developerssupporting
confidence: 79%
“…These results are similar to a study that was carried out 15 years previous, which indicates stagnation in engineer's mindsets [17]. Beyond interviews, a discourse analysis of two mobile developer forums for privacy relevant conversations found that developers of these forums were concerned about how third-parties are collecting data, the privacy implications of features requested by end-users, and the legal consequences of their actions [60].…”
Section: Privacy and Developerssupporting
confidence: 79%
“…They concluded that developer forums such as the iPhoneDevSDK forum and the Android XDA forums act as quasi-regulators, setting privacy expectations for applications to be published on their platform stores and thereby guiding app developers' privacy efforts. A complementary study showed that certain work practices, such as navigating the platform's approval or user requests, can act as levers for privacy discourse, triggering larger debates on privacy and ethical requirements in general (Shilton and Greene 2017).…”
mentioning
confidence: 99%
“…Some values in design scholarship analyzes technologies themselves to understand values that they do, or don't, support well (Brey 2000;Friedman and Nissenbaum 1996;Winner 1980). Other ViD scholars study the people developing technologies to understand their human and organizational motivations and the ways those relate to design decisions (Spiekdermann et al 2018;JafariNaimi et al 2015;Manders-Huits and Zimmer 2009;Shilton 2018;Shilton and Greene 2019). A third stream of ViD scholarship builds new technologies that purposefully center particular human values or ethics (Friedman et al 2017).…”
Section: Values In Designmentioning
confidence: 99%